2011
DOI: 10.1258/la.2011.011022
|View full text |Cite
|
Sign up to set email alerts
|

The morphology and haemodynamics of the rabbit renal artery: evaluation by conventional and contrast-enhanced ultrasonography

Abstract: The purpose of this study was to test the morphology and haemodynamics of the renal artery in the rabbit as evaluated by conventional and contrast-enhanced ultrasonography (CEUS). The morphology and haemodynamics of the rabbit renal artery, including the diameter, which were measured using B-mode ultrasonography (US), colour Doppler US and CEUS, and systolic velocity, diastolic velocity and resistive index (RI) were measured using pulsed wave Doppler US. CEUS was used to measure the renal artery diameter: 0.21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Pope et al (1996) reported a 95% confidence interval (CI) from 0.43 to 0.63 (0.53 ± 0.05) in another porcine study. Baseline values in studies on rabbits vary between 0.51 ± 0.04 and 0.54 ± 0.11 (Chu et al, 2011;Kaya et al, 2010;). An intrarenal RI range of 0.52 -0.73 have been reported for healthy dogs (Nyland et al, 1993), and of 0.44 -0.71 for healthy cats (Rivers et al, 1996).…”
Section: Animalsmentioning
confidence: 99%
“…Pope et al (1996) reported a 95% confidence interval (CI) from 0.43 to 0.63 (0.53 ± 0.05) in another porcine study. Baseline values in studies on rabbits vary between 0.51 ± 0.04 and 0.54 ± 0.11 (Chu et al, 2011;Kaya et al, 2010;). An intrarenal RI range of 0.52 -0.73 have been reported for healthy dogs (Nyland et al, 1993), and of 0.44 -0.71 for healthy cats (Rivers et al, 1996).…”
Section: Animalsmentioning
confidence: 99%
“…Chu et al . (4) presented findings concerning the value of the RI in the rabbit renal artery, discovering no adverse effects following the administration of amobarbital sodium during anaesthesia. In research on rabbits, propofol had minimal effect on haemodynamics, whereas combinations of xylazine-ketamine and thiopental resulted in a significant decrease in RI value (10).…”
Section: Discussionmentioning
confidence: 99%